Silene as a model system in ecology and evolution. - Bernasconi, G; Antonovics, J; Biere, A; Charlesworth, D; Delph, L; Filatov, D; Giraud, T; Hood, M; Marais, G; McCauley, D; Pannell, J; Shykoff, J; et al. (2009)
The genus Silene, studied by Darwin, Mendel and other early scientists, is re-emerging as a system for studying interrelated questions in ecology, evolution and developmental biology. These questions include sex chromosome evolution, epigenetic control of sex expression, genomic conflict and speciation. Its well-studied interactions with the pathogen Microbotryum has made Silene a model for the evolution and dynamics of disease in natural systems, and its interactions with herbivores have increased our understanding of multi-trophic ecological processes and the evolution of invasiveness. Molecular tools are now providing new approaches to many of these classical yet unresolved problems, and new progress is being made through combining phylogenetic, genomic and molecular evolutionary studies with ecological and phenotypic data.